The Availability of the Basic Vegetation Materials for the Bird Nest of Paradisaea minor jobiensis in Yapen, Islands Papua - Wazaraka, Zainal Arifin; Raunsay, Edoward K.; Kameubun, Konstantina M. B. (Jurnal Sylva Lestari, 2019)
The existence of cendrawasih (Paradisaea minor jobiensis Rothschild 1897) has been endangered due to destruction its habitats and wild hunting, hence conservation of its habitats is urgently needed. The objective of this study was to determine the availability of vegetation materials for creating the nests as an effort for the conservation of P. minor jobiensis in Imboriawi Forest, Barawai, Yapen Islands, Papua. Data were collected using the method of line compartment. Vegetation at seedling, sapling, pole and tree levels were measured and analyzed to determine the availability of plant species as the materials for creating bird nest. The results of vegetation analysis revealed 60 species at seedling level, 43 species at sapling level, 68 species at pole level, and 74 species at tree level with high diversity index values (H') of 3.68, 3.32, 3.87, and 3.87 for seedling, sapling, pole, and tree levels, respectively. The results also revealed that vegetation used as a materials of nest of P. minor jobiensis in Imbowiari Forest is Bidens spilosa, Macaranga mappa, Timonius timon and Ficus septica. The four species at seedling, sapling, poles, and tree levels have low diversity index values (H'= 1) but can be used as indicators of making a nest in a sustainable way. Keywords: bird nest, conservation, Paradisaea minor jobiensis, vegetation analysis